Investigaton of the Effects of Cutting Parameters on The Surface Roughness, Tool Temperature and Thrust Force in Drilling of AA 7075-T6 Alloy - Caydas, Ulas; Celik, Mahmut (Gazi Univ, 2017)
In this study, the AA 7075 - T6 aluminum alloy was subjected to continuous drilling process with K 20 grade carbide tools under dry machining conditions. In the experiments, the cutting speed (V) was fixed, while tool feed rate (f) and tool point angle (theta) were changed in certain intervals to experimentally explore their effects on the surface roughness, thrust force and tool bit temperature. Consequently, optimum parameter conditions were determined and evaluated for the best drilling of AA 7075 - T6 alloy.
Keywords: AA 7075 - T6; Tool Temperature; Surface Roughness; Drilling; Thrust Force